The Bible, King James version, Book 25: Lamentations - Anonymous (Salt Lake City, UT : Project Gutenberg, 2005)
"The Bible, King James version, Book 25: Lamentations" by Anonymous is a collection of poetic laments composed shortly after 586 BCE. Five poems mourn Jerusalem's destruction, presenting the catastrophe as divine punishment for communal sin. The tone is devastatingly bleak$1 (BGod remains silent, suffering overwhelms, and hope flickers dimly. Yet the author doesn't blame God, instead affirming divine righteousness while wrestling with an agonizing possibility: perhaps God has finally rejected his people forever. Will mercy arrive, or has abandonment become permanent? (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Book_of_Lamentations
Release date is 2005-04-01
This eBook was produced by David Widger with the help of Derek Andrew's text from January 1992 and the work of Bryan Taylor in November 2002
Keywords: Bible. Lamentations